Immunohistochemical analysis of desmoid tumours. Issue 11 (27th October 2005) - Leithner, A; Gapp, M; Radl, R; Pascher, A; Krippl, P; Leithner, K; Windhager, R; Beham, A
Abstract : Background/Aims: Although the standard treatment for desmoid tumours is complete surgical resection with wide margins, the optimal adjuvant treatment for recurrent or inoperable disease is unclear, often being based on sporadic immunohistochemical reports with a low number of cases. Therefore, a large immunohistochemical study was performed, to provide a theoretical basis for adjuvant treatment regimens. Methods: One hundred and sixteen tissue samples from 80 patients (49 female, 31 male; mean age, 34 years; range, 0–83) with desmoid tumours (46 extra-abdominal, 21 abdominal, 13 intra-abdominal) were tested for oestrogen receptors α and β, progesterone and androgen receptors, and somatostatin, in addition to HER2, cathepsin D, Ki-67, and c-KIT by immunohistochemistry. Results: All samples were negative for oestrogen receptor α, HER2, and the progesterone receptor. Positive staining for the androgen receptor was found in six extra-abdominal cases. Staining for oestrogen receptor β was positive in four extra-abdominal, two abdominal, and one intra-abdominal case. Staining for somatostatin was positive in six extra-abdominal, two abdominal, and one intra-abdominal case, and staining for cathepsin D was positive in all cases. Positive staining for Ki-67 was found in 14 extra-abdominal, three abdominal, and three intra-abdominal cases. C-KIT was detectable in one abdominal case only. Conclusions: The data from this immunohistochemical study show that the published effects of antioestrogens and imatinib mesylate in the treatment of aggressive fibromatoses may not be attributable to oestrogen receptor α or c-KIT expression.